A projektpedagógia metodikája és megvalósulásának egy reprezentatív példája: a pécsi Leőwey Klára Gimnázium VIZED Projektje - Schnell, Zsuzsanna; Zalay, Szabolcs; Gombás, Ildikó (Kultúratudományi Szemle, 2022)
The Project Method and a representative example of its implementation in the „Y’our Water” project of Leőwey Klára high school in Pécs Zsuzsanna Schnell – Szabolcs, Zalay – Ildikó, Gombás Today’s educational sciences face the challenge of finding and creating a methodology that is feasible in the 21st century, that is relevant for the new generations and serves purposes that bring on social change. The implementation of such 21st century competencies is of key importance for today’s professionals. Project pedagogy offers a framework for this need and provides several useful practices for future pedagogical methods. Our article describes the challenges of modern education, gives an overview of 21st century needs and competencies and provides an example for the implementation of these in the VIZED (“Y’our Water”) Project of Leőwey High School in Pécs, the partner institute of the University of Pécs and our Faculty.